Cardiology for veterinary technicians and nurses - Durham, H. Edward, Jr. (Hoboken, NJ : Wiley-Blackwell, 2017)
'Cardiology for Veterinary Technicians and Nurses is a comprehensive resource for veterinary technicians and nurses working with cardiovascular patients in veterinary practice. Offers a complete reference to veterinary cardiology targeted at veterinary technicians and nurses, summarizing fundamental knowledge on cardiovascular disease Covers dogs, cats, horses, ruminants, and camelids Provides information ranging from introductory to advanced for a thorough guide to cardiac conditions Presents detailed procedures for common cardiac catheterization techniques, including supplies required Includes photographs and illustrations to depict the concepts described'--Provided by publisher.
Includes bibliographical references and index.
Machine generated contents note: Introduction. Section I-Cardiac Anatomy, Physiology and Dysfunction. Chapter 1. Cardiac Anatomy. Chapter 2. Basic Cardiac Physiology. Cardiac Cycle. Blood Pressure Regulation. Chapter 3. The Pathophysiology of Heart Failure. Section II-Diagnostics. Chapter 4. History and Physical Exam. Chapter 5. Electrocardiography: Principles and Use. Basic Theory. Arrhythmia recognition. Chapter 6. Thoracic Radiography. Chapter 7. Echocardiography. Basic Theory. Echocardiographic Views. Measurements. Chapter 8. Blood Pressure Measurement. Chapter 9. Angiography. Equipment. Chapter 10. Cardiac Specific Biomarkers. Section III-Diseases. Chapter 10. Acquired Disease. Dilated Cardiomyopathy. Acquired Valve Disease. Feline Cardiomyopathies. Chapter 11. Congenital Disease. Stenosis. Shunts. Chapter 12. Pericardial Disease and Cardiac Neoplasia. Section IV-Therapies and Interventions. Chapter 13. Cardiac Drugs. Antiarrhythmics. Drugs for Heart Failure. Chapter 14. Treatment of Congestive Heart Failure. Acute Therapy. Chronic Therapy. Chapter 15. Interventional Procedures. Balloon Valvuloplasty. PDA occlusion. Bradyarrhythmia Pacemaker Therapy. Other Procedures-. Section V-Large Animal Cardiology. Chapter 16. Equine. Chapter 17. Ruminants.
Print version record and CIP data provided by publisher; resource not viewed.
Keywords: Veterinary cardiology; TECHNOLOGY & ENGINEERING / Agriculture / Animal Husbandry; Heart Diseases -- veterinary; Animal Technicians; Electronic books